Leadership and governance, financing, and coordination and their impact on the operationalization of health interventions in the humanitarian-development nexus in South Sudan. - Amany Qaddour; Lauren Yan; Dan Wendo; Laura Elisama; Christopher Lindahl; Paul Spiegel (PLoS ONE)
South Sudan ranks among the most fragile nations in the world. Protracted conflict and recurrent shocks have weakened its health system and contributed to high maternal and child mortality rates, despite large amounts of humanitarian and development assistance injected into the country since independence. Factors related to the leadership and governance, financing, and coordination of health services impact the feasibility of implementing the humanitarian-development nexus (HDN). Researchers employed a qualitative case study design drawing from document reviews and individual and group semi-structured interviews with humanitarian and development stakeholders in South Sudan (Juba capital and Bor town). Data was analyzed and findings were synthesized and organized into distinct themes. Forty-one interviews were conducted with 68 participants between November 2022 and January 2023, and 57 documents were analyzed. Findings showed that limited government investment in the health sector has perpetuated reliance on international assistance, and barriers to engagement with government counterparts have restricted coordination. Some nascent HDN coordination platforms exist with minimal political buy-in. Recent reductions in development health funding have complicated progress towards longer-term development objectives, including health systems strengthening. Structural barriers within multi-mandate agencies and differences in programming cycles, funding, and reporting contribute to silos. Continued fragility, a restricted operational environment, shrinking funds, and fragmented coordination have made it challenging to plan, finance, and implement HDN-health interventions. Informal efforts to bridge silos between humanitarian and development actors should become more formalized to use resources more efficiently. Despite certain restrictions in engagement with government, coordination and planning at the sub-national level may still be feasible. Such engagement should be enhanced to ensure sustainability of health services. Investment in health systems strengthening and resilience by humanitarian and development actors should enable communities to absorb recurrent shocks and prevent backsliding in health provision.